Baseline Flight Potential of Euschistus servus (Hemiptera: Pentatomidae) and Its Implications on Local Dispersal. Issue 3 (20th April 2020) - Babu, Arun; Del Pozo-Valdivia, Alejandro I; Reisig, Dominic D
Abstract: The brown stink bug, Euschistus servus (Say), is a damaging pest of multiple crops in the southeastern United States. In addition to crops, both the weedy field borders and wooded areas of a typical farmscape in this region harbor E. servus host plants, many of which are temporally and spatially limiting in availability or nutritional suitability. Therefore, local dispersal is required so that individuals efficiently track and utilize host resources. This research sought to establish the baseline flight capacity of adult E. servus across the season in relation to body weight, sex, and plant host use with a flight mill system. Across this 2-yr study, among the individuals with a flight response in the flight mill, 90.1% of individuals flew in a range of >0–1 km, with an individual maximum flight distance of 15.9 km. In 2017, mean total distance flown varied across the season. Except for the individuals collected from corn in 2019, during both 2017 and 2019, the highest numerical mean flight potential occurred soon after overwintering emergence and a relatively low flight potential occurred during the cropping season. Individuals collected from wheat, corn, and early season weeds lost a higher proportion of body weight after flight than did individuals from soybean and late season weeds. The baseline dispersal potential information generated from this study can be extrapolated to the farmscape level aiming to develop, plan, and implement E. servus management programs.